Síndrome por deleción 18p diagnosticado por array de hibridación genómica comparada. Presentación de un caso con fenotipo leve (2016)
Deletion on the short arm of chromosome 18 is an infrequent syndrome and it is characterized by the following features: mental retardation, growth retardation, craniofacial malformations such as large ears, microcephaly, and short neck. The phenotypical spectrum is a wide range of abnormalities including minor congenital abnormalities to holoprosencephaly. We present a case of a 10 year old girl who is found to have a deletion on the short arm of chromosome 18 (18p11.32-p11.21), by conventional cytogenetic analysis and comparative genomic hybridization.